Antipsychotic Polypharmacy-Related Cardiovascular Morbidity and Mortality: A Comprehensive Review - Amber N. Edinoff; Emily D. Ellis; Laura M. Nussdorf; Taylor W. Hill; Elyse M. Cornett; Adam M. Kaye; Alan D. Kaye (MDPI AG, 2022)
Schizophrenia is a psychotic disorder that exists at the more extreme end of a spectrum of diseases, and significantly affects daily functioning. Cardiovascular adverse effects of antipsychotic medications are well known, and include changes in blood pressure and arrhythmias. Sudden cardiac death is the leading cause of death worldwide, and antipsychotic medications are associated with numerous cardiac side effects. A possible link exists between antipsychotic medications and sudden cardiac death. Common prescribing patterns that may influence cardiovascular events include the use of multiple antipsychotics and/or additional drugs commonly prescribed to patients on antipsychotics. The results of this review reflect an association between antipsychotic drugs and increased risk of ventricular arrhythmias and sudden cardiac death by iatrogenic prolongation of the QTc interval. QTc prolongation and sudden cardiac death exist in patients taking antipsychotic monotherapy. The risk increases for the concomitant use of specific drugs that prolong the QTc interval, such as opioids, antibiotics, and illicit drugs. However, evidence suggests that QTc intervals may not adequately predict sudden cardiac death. In considering the findings of this narrative review, we conclude that it is unclear whether there is a precise association between antipsychotic polypharmacy and sudden cardiac death with QTc interval changes. The present narrative review warrants further research on this important potential association.